A comparative study on the functional outcome of intertrochanteric fractures treated by proximal femoral nailing or dynamic hip screw fixation - Chandy, Gineshmon; S., Saju (International Journal of Research in Orthopaedics, 2020)
Background: Intertrochanteric fractures are one of the commonly occurring injuries in elderly patients and are high among females and those with osteoporosis. They were treated with either dynamic hip screw (DHS) fixation or proximal femoral nailing (PFNA2) here at our institution. The study was conducted in order to find which method of surgical fixation has better functional outcome. Methods: Total 96 patients of intertrochanteric fractures admitted during the study period of November 2017 to April 2019 were included for the study. These patients were randomly divided into two groups; DHS was used as implant in group1 and PFNA2 in group 2. Postoperatively patients were followed up after 1 month, 3months and 6 months of the surgery and were assessed using Harris hip score. Results: Harris hip score was higher with PFNA2 group compared to DHS group in all follow-ups. In unstable fractures DHS group had poor outcome compared to PFNA2. Radiological union occurred in 27.1 % cases by 3 months and 72.9% cases by 6 months with DHS whereas 70.8% and 97.9% respectively with PFNA2. Conclusions: PFNA2 gives a better functional outcome when compared to DHS. Even though DHS gives good functional outcome in stable fractures it is not so in the case of unstable fractures. The radiological union also is faster with proximal femoral nailing. Hence in our opinion PFNA2 can be the better fixation device compared to DHS especially in unstable fractures.